Effect of Electrolytes and Microbial Culture toward Electricity Generation Utilizing Tempe Wastewater in Microbial Fuel Cell - Tania Surya Utami (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Demand for electricity has become a crucial requirement of Indonesian society. Resources, which generate electrical energy such as fossil fuel, is predicted to run out within the next dozen years. Microbial Fuel Cell is a development of the latest technology that uses microbes to break down a substrate. This activity will cause potential difference and generate electricity. Microbes which generate electricity could be derived from pure culture and mixed culture. In this study, mixed culture of tempe wastewater microbes is used by adding electrolytes variation which are ammonium chloride-potassium chloride, potassium permanganate, and potassium persulfate in a single chamber reactor. The optimum voltage and power density are 62,09 mV and 3,01 mW/m2 when using potassium persulfate. Result of this research are compared to others research which using pure culture of L.bulgaricus by adding electrolytes variation which are potassium ferrycianide and potassium permanganate. In additional, utilization of potassium permanganat in mixed culture of tempe wastewater microbes and pure culture of L.bulgaricus are also compared to each other. The optimum voltage and power density of those comparison are 457 mV and 167,7 mW/m2 when using potassium permanganat in pure culture of L.bulgaricus.